Cu-Cr-Ni corrosion-resistant steel bar and preparation method thereof
By adding alloy elements such as Cu, Cr and Ni to the corrosion-resistant steel and optimizing the smelting process, Cu-Cr-Ni-based corrosion-resistant steel bars were prepared, which solved the problem of insufficient corrosion resistance of existing corrosion-resistant steel varieties under different corrosion environments, and achieved high-performance and low-cost corrosion-resistant steel bars.
Patent Information
- Application Number
- CN202411312718.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-03-04
AI Technical Summary
The existing corrosion-resistant steel varieties are not corrosion-resistant enough when facing different corrosion environments, and the smelting process is complex and costly, making it difficult to meet the demand for corrosion-resistant steel bars in infrastructure construction.
Cu-Cr-Ni-based corrosion-resistant steel bars are used to optimize the smelting process by adding alloy elements Cu, Cr and Ni, including heating to austenite homogenization temperature and insulation, rough rolling, pre-finishing rolling and finishing rolling, and finally air-cooling to room temperature.
The excellent mechanical properties of Cu-Cr-Ni-based corrosion-resistant steel bars, excellent resistance to marine atmospheric corrosion and seawater corrosion resistance are achieved, reducing production costs and simplifying the smelting process.
Smart Images

Figure CN119553183A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrosion-resistant steel, and in particular relates to a Cu-Cr-Ni series corrosion-resistant steel bar and a preparation method thereof. Background Art
[0002] The direct economic losses caused by corrosion in countries around the world each year account for about 2% to 4% of the gross national product, of which one-third comes from marine corrosion. Factors such as salt, humidity, oxygen and climate change in seawater can cause serious corrosion damage to metal materials. - The radius is small, the penetration is strong, and the conductivity of the medium is increased, the erosion of the corrosive medium is enhanced, and the corrosion of steel is strongly induced. The problem of marine atmospheric corrosion on steel is a major bottleneck in building a strong maritime nation, and the application of traditional weathering steel is limited.
[0003] In response to the problem of steel bar corrosion, domestic and foreign scholars have conducted many studies and developed various anti-corrosion technologies. They mainly include coatings, steel bar rust inhibitors, epoxy resin coatings, stainless steel coated steel bars, etc. By taking appropriate protective measures, the corrosion of steel bars can be effectively slowed down and their service life can be extended. Traditional steel bar anti-corrosion methods mostly start from the external environment. On the basis of not changing the ordinary carbon bar substrate, they slow down the erosion of the external medium on the steel bars to achieve the purpose of preventing the corrosion of the steel bars. This method is complex to operate and expensive. Compared with traditional protection methods, corrosion-resistant steel bars prepared by alloying regulation have become the focus of attention due to their low price and strong corrosion resistance.
[0004] The publication number is CN112391572A, and the title is a patented technology for the preparation process of Cu-Cr corrosion-resistant steel bars. By adding copper and chromium to the components, the formation of intermetallic compounds is promoted, and the probability of precipitation of chromium carbide in some high free energy areas (such as pitting areas, dislocation areas or interface areas) is reduced. The holding time for the formation of chromium carbide is selected to prevent overheating and rapid cooling, so that carbon does not have time to precipitate; the formation of carbides such as chromium carbide is inhibited; water quenching is performed to quickly pass through the sensitization temperature zone so that the alloy retains the structure of Cu-Cr-containing intermetallic compounds. This method has too high requirements for smelting and each process. It is necessary to control the specific ratio of Cr / Cu and strictly control the content of impurity elements, otherwise Cu will form inclusions with it, and the holding time is not disclosed in the patent.
[0005] The patented technology with publication number CN112662948A and titled "RE-Cr-Cu composite corrosion-resistant steel and its preparation method" adds RE-Cr-Cu composite to corrosion-resistant steel, aggregates at interfaces such as phase boundaries and grain boundaries, reduces interfacial energy, and avoids local corrosion; utilizes RE-Cr-Cu composite strengthening to stabilize and compact the surface rust layer structure and reduce the electrode potential difference between it and the matrix. Rare earth elements are mainly used to refine dendrites and change the properties, morphology and distribution of inclusions, but the role of rare earth elements is not specifically explained in this method. It is only explained with the conventional idea of reducing interfacial energy, stabilizing rust layer structure and reducing electrode potential difference, and rare earth elements are expensive. The process requirements in this patented technology are also relatively cumbersome.
[0006] The patented technology with the authorization announcement number CN112795844B and the title "A low-carbon Cr-Ni high-strength corrosion-resistant steel and its preparation method" reduces the carbon content so that carbides are not easily formed in the steel, and obtains the goal of ferrite + tempered martensite, yield strength greater than 360MPa, tensile strength greater than 570MPa, and elongation of 20.0% to 29.0%. This method reduces the carbon content, resulting in poor mechanical properties, and at the same time adds a large amount of alloying elements, with the maximum addition of Cr elements reaching 9.8wt% and Ni elements ranging from 1.1 to 1.9wt%, with high costs and low economic benefits.
[0007] The patented technology with publication number CN113897472A and titled "A Process for Preparing Cu-Cr Corrosion-Resistant Steel Bars" uses a central controller to adjust the following parameters during refining in a ladle refining furnace to improve the corrosion resistance of the prepared steel bars. This method is only adjusted based on preset values, and the specific element composition and performance indicators are not disclosed.
[0008] In summary, the existing corrosion-resistant steel varieties still have a lot of room for improvement. With the development of my country's infrastructure, it is urgent to develop corrosion-resistant steel bars that can adapt to different corrosion environments. Therefore, it is necessary to develop a Cu-Cr-Ni corrosion-resistant steel bar and its preparation method to improve the corrosion resistance of corrosion-resistant steel, optimize the smelting process, and reduce production costs. Summary of the invention
[0009] The object of the present invention is to provide a Cu-Cr-Ni series corrosion-resistant steel bar with simple process and low preparation cost and a preparation method thereof. The Cu-Cr-Ni series corrosion-resistant steel bar prepared by the method has excellent mechanical properties, excellent marine atmospheric corrosion resistance and excellent seawater corrosion resistance.
[0010] In view of this, one aspect of the present invention provides a Cu-Cr-Ni corrosion-resistant steel bar, wherein the chemical composition of the Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0011] C: 0.10~0.11wt%, Si: 0.3~0.5wt%, Mn: 1.1~1.5wt%, Cu: 0.3~0.6wt%, Cr: 0.7~0.9wt%, Ni: 0.2~0.4wt%, V: 0.01~0.03wt%, and the rest are Fe and unavoidable impurities.
[0012] Further preferably, the C: 0.105-0.11wt%, Si: 0.3-0.4wt%, Mn: 1.4-1.5wt%, Cu: 0.3-0.4wt%, Cr: 0.7-0.9wt%, Ni: 0.2-0.4wt%, V: 0.01-0.03wt%, and the rest are Fe and unavoidable impurities.
[0013] Furthermore, the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar is ferrite+pearlite+a small amount of bainite.
[0014] Furthermore, the yield strength of the Cu-Cr-Ni corrosion-resistant steel bar is 530MPa-580MPa, the tensile strength is 700MPa-750MPa, the hardness is 250HV-280HV, and the elongation is 16%-19%.
[0015] Furthermore, in the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar, the volume fraction of ferrite is 35% to 45%, the volume fraction of pearlite is 45% to 58%, and the volume fraction of bainite is 7% to 18%.
[0016] Furthermore, the average corrosion rate of the Cu-Cr-Ni corrosion-resistant steel bar in the 15-day immersion test was 2.6537*10 -2 ~2.8815*10 -2 g / (m 2 h).
[0017] Furthermore, the self-corrosion current of the Cu-Cr-Ni corrosion-resistant steel bar is 5.37*10 -5 A / cm 2 , the self-corrosion voltage is -0.674V.
[0018] Furthermore, the soaking solution of the soaking experiment was a 3.5 wt % NaCl solution, and the solution was replaced every three days.
[0019] On the other hand, the present invention also discloses a method for preparing a Cu-Cr-Ni corrosion-resistant steel bar, comprising:
[0020] Step 1: heating the ingot to the austenite homogenization temperature and keeping the temperature to obtain a homogenized steel ingot;
[0021] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0022] Step 3: After rolling the billet to the target thickness, cool it to room temperature.
[0023] Furthermore, in step 1, the austenite homogenization temperature is controlled to be 1150-1500°C.
[0024] Furthermore, in step 1, the insulation time is 30 to 50 minutes.
[0025] Furthermore, in step 2, the starting rolling temperature is not less than 900°C, the rough rolling temperature is 1050±20°C, the pre-finishing rolling temperature is 910±20°C, the finishing rolling temperature is 850±20°C, the cooling bed inlet temperature is 850±20°C, and the final rolling temperature is 850-950°C.
[0026] Furthermore, in step 3, the cooling method is air cooling.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The addition of alloying elements Cu, Cr and Ni can effectively reduce the self-corrosion current and self-corrosion voltage of corrosion-resistant steel bars and the corrosion rate under immersion conditions. The addition of alloying elements causes the self-corrosion potential of corrosion-resistant steel bars to move in a more positive direction, improve the stability of corrosion-resistant steel bars and reduce their corrosion rate. The self-corrosion current is 5.37*10 -5 A / cm 2 The self-corrosion voltage is -0.674V. In the 15-day immersion accelerated corrosion test, the average corrosion rate is 2.6537*10 -2 ~2.8815*10 - 2 g / (m 2 h).
[0029] (2) The addition of alloying elements Cu, Cr and Ni gives Cu-Cr-Ni corrosion-resistant steel bars excellent mechanical properties. The microstructure is ferrite + pearlite + a small amount of bainite, which ensures corrosion resistance while providing excellent mechanical properties. The yield strength is 530MPa~580MPa, the tensile strength is 700MPa~750MPa, the hardness is 250HV~280HV, and the elongation is 16%~19%.
[0030] (3) The addition of alloying elements Cu, Cr and Ni helps to form a more uniform, dense and stable protective rust layer on the surface of corrosion-resistant steel bars, which can effectively prevent corrosive media, especially Cl - It penetrates the rust layer and reaches the substrate, causing corrosion.
[0031] (4) The Cu-Cr-Ni corrosion-resistant steel bars of the present invention have excellent seawater corrosion resistance and are superior to the corrosion resistance of HRB400E.
[0032] (5) The alloying elements added in the present invention are low in content, which greatly reduces the cost output, has high economic benefits, and has a simple smelting process. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The microstructure of the Cu-Cr-Ni corrosion-resistant steel bar in Example 1 is obtained by SEM electron microscope at a magnification of 300 times;
[0034] Figure 2 The microstructure of the Cu-Cr-Ni corrosion-resistant steel bar in Example 1 is obtained by SEM electron microscope at a magnification of 1000 times;
[0035] Figure 3 The metallographic microscope microstructure diagram of the Cu-Cr-Ni corrosion-resistant steel bar in Example 1;
[0036] Figure 4 The corrosion morphology macrograph of the corrosion sample after the Cu-Cr-Ni corrosion-resistant steel bar and the ordinary steel bar in Example 1 were immersed in a NaCl solution with a concentration of 3.5wt% for 15 days;
[0037] Figure 5 The scanning electron microscope image of the cross section of the rust layer of the corrosion sample after the Cu-Cr-Ni corrosion-resistant steel bar in Example 1 was immersed in a NaCl solution with a concentration of 3.5wt% for 15 days;
[0038] Figure 6 This is a scanning electron microscope image of the rust layer surface of the corrosion sample after the Cu-Cr-Ni corrosion-resistant steel bar in Example 1 was immersed in a NaCl solution with a concentration of 3.5wt% for 15 days. DETAILED DESCRIPTION
[0039] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thorough and comprehensive.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0041] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of the Cu-Cr-Ni corrosion-resistant steel bar comprising:
[0042] C: 0.10~0.11wt%, Si: 0.3~0.5wt%, Mn: 1.1~1.5wt%, Cu: 0.3~0.6wt%, Cr: 0.7~0.9wt%, Ni: 0.2~0.4wt%, V: 0.01~0.03wt%, and the rest are Fe and unavoidable impurities.
[0043] Further preferably, the C: 0.105-0.11wt%, Si: 0.3-0.4wt%, Mn: 1.4-1.5wt%, Cu: 0.3-0.4wt%, Cr: 0.7-0.9wt%, Ni: 0.2-0.4wt%, V: 0.01-0.03wt%, and the rest are Fe and unavoidable impurities.
[0044] Furthermore, the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar is ferrite+pearlite+a small amount of bainite.
[0045] Furthermore, the yield strength of the Cu-Cr-Ni corrosion-resistant steel bar is 530MPa-580MPa, the tensile strength is 700MPa-750MPa, the hardness is 250HV-280HV, and the elongation is 16%-19%.
[0046] Furthermore, in the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar, the volume fraction of ferrite is 35% to 45%, the volume fraction of pearlite is 45% to 58%, and the volume fraction of bainite is 7% to 18%.
[0047] Furthermore, the average corrosion rate of the Cu-Cr-Ni corrosion-resistant steel bar in the 15-day immersion test was 2.6537*10 -2 ~2.8815*10 -2 g / (m 2 h).
[0048] Furthermore, the self-corrosion current of the Cu-Cr-Ni corrosion-resistant steel bar is 5.37*10 -5 A / cm 2 , the self-corrosion voltage is -0.674V.
[0049] Furthermore, the soaking solution of the soaking experiment was a 3.5 wt % NaCl solution, and the solution was replaced every three days.
[0050] On the other hand, the present invention also discloses a method for preparing a Cu-Cr-Ni corrosion-resistant steel bar, comprising:
[0051] Step 1: heating the ingot to the austenite homogenization temperature and keeping the temperature to obtain a homogenized steel ingot;
[0052] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0053] Step 3: After rolling the billet to the target thickness, cool it to room temperature.
[0054] Furthermore, in step 1, the austenite homogenization temperature is controlled to be 1150-1500°C.
[0055] Furthermore, in step 1, the insulation time is 30 to 50 minutes.
[0056] Furthermore, in step 2, the starting rolling temperature is not less than 900°C, the rough rolling temperature is 1050±20°C, the pre-finishing rolling temperature is 910±20°C, the finishing rolling temperature is 850±20°C, the cooling bed inlet temperature is 850±20°C, and the final rolling temperature is 850-950°C.
[0057] Furthermore, in step 3, the cooling method is air cooling.
[0058] In order to evaluate the seawater corrosion resistance of corrosion-resistant steel bars, the present invention uses an immersion test to simulate the seawater corrosion environment. The test conditions of the immersion test in the present invention are: putting the sample into a 3.5wt% NaCl solution at room temperature, changing the solution every 3 days, and the total cycle is 15 days.
[0059] The test conditions for corrosion rate are: corrosion rate = (mass loss / original mass) × (time / exposure area);
[0060] The calculation formula of relative corrosion rate is: (corrosion rate of sample - corrosion rate of comparison sample) / corrosion rate of comparison sample*100%.
[0061] Example 1
[0062] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.11wt%, Si: 0.38wt%, Mn: 1.29wt%, Cu: 0.56wt%, Cr: 0.90wt%, Ni: 0.39wt%, V: 0.021wt%, and the rest is Fe and unavoidable impurities.
[0063] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0064] Step 1: heating the ingot to 1150°C until the austenite is homogenized and keeping the temperature to obtain a homogenized steel ingot;
[0065] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0066] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0067] The starting rolling temperature is 1000℃, the rough rolling temperature is 1030℃, the pre-finishing rolling temperature is 920℃, the finishing rolling temperature is 870℃, the cooling bed inlet temperature is 840℃, and the final rolling temperature is 900℃.
[0068] The yield strength, tensile strength, hardness, elongation and corrosion rate were tested, and the results are shown in Table 1.
[0069] Its yield strength, tensile strength, hardness, elongation and corrosion rate are 560.75MPa, 727.35MPa, 263.5HV, 17.89%, 2.7253*10 -2 g / (m 2 h).
[0070] The volume fractions of ferrite, pearlite and bainite are 43%, 48% and 7% respectively.
[0071] like Figure 1 and Figure 2 As shown in the figure, the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar prepared in this embodiment is obtained by SEM electron microscope at different magnifications. It can be seen from the figure that the structure of the Cu-Cr-Ni corrosion-resistant steel bar in this embodiment is ferrite, pearlite and a small amount of bainite, and the improvement of its strength may be due to the refinement and fragmentation of pearlite; Figure 3 The metallographic microscope microstructure diagram of the Cu-Cr-Ni corrosion-resistant steel bar prepared in this embodiment. It can be seen from the figure that the Cu-Cr-Ni corrosion-resistant steel bar in this embodiment has a uniform structure. Figure 5 From the cross section of the rust layer, it can be seen that the rust layer is closely bonded to the substrate, the rust layer is flat, has few pores and cracks, and has a strong protective effect on the substrate. Figure 6 It can be seen from the surface of the rust layer that the rust layer has good density, the smoothest surface, small cracks and gaps, and good effect in protecting the substrate.
[0072] Example 2
[0073] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.1wt%, Si: 0.3wt%, Mn: 1.1wt%, Cu: 0.3wt%, Cr: 0.7wt%, Ni: 0.2wt%, V: 0.01wt%, and the rest is Fe and unavoidable impurities.
[0074] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0075] Step 1: heating the ingot to 1200°C until the austenite is homogenized and keeping the temperature for 50 minutes to obtain a homogenized steel ingot;
[0076] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0077] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0078] The starting rolling temperature is 900℃, the rough rolling temperature is 1050℃, the pre-finishing rolling temperature is 900℃, the finishing rolling temperature is 850℃, the cooling bed inlet temperature is 850℃, and the final rolling temperature is 850℃.
[0079] Example 3
[0080] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.11wt%, Si: 0.5wt%, Mn: 1.5wt%, Cu: 0.6wt%, Cr: 0.9wt%, Ni: 0.4wt%, V: 0.03wt%, and the rest is Fe and unavoidable impurities.
[0081] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0082] Step 1: heating the ingot to 1150°C until the austenite is homogenized and keeping the temperature for 50 minutes to obtain a homogenized steel ingot;
[0083] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0084] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0085] The starting rolling temperature is 1000℃, the rough rolling temperature is 1070℃, the pre-finishing rolling temperature is 890℃, the finishing rolling temperature is 830℃, the cooling bed inlet temperature is 830℃, and the final rolling temperature is 900℃.
[0086] Example 4
[0087] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.105wt%, Si: 0.4wt%, Mn: 1.3wt%, Cu: 0.5wt%, Cr: 0.8wt%, Ni: 0.3wt%, V: 0.02wt%, and the rest is Fe and unavoidable impurities.
[0088] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0089] Step 1: heating the ingot to 1300°C until the austenite is homogenized and keeping the temperature for 40 minutes to obtain a homogenized steel ingot;
[0090] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0091] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0092] The starting rolling temperature is 1000℃, the rough rolling temperature is 1050℃, the pre-finishing rolling temperature is 930℃, the finishing rolling temperature is 870℃, the cooling bed inlet temperature is 870℃, and the final rolling temperature is 950℃.
[0093] Example 5
[0094] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.1wt%, Si: 0.35wt%, Mn: 1.2wt%, Cu: 0.4wt%, Cr: 0.75wt%, Ni: 0.25wt%, V: 0.015wt%, and the rest is Fe and unavoidable impurities.
[0095] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0096] Step 1: heating the ingot to 1400°C until the austenite is homogenized and keeping the temperature for 30 minutes to obtain a homogenized steel ingot;
[0097] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0098] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0099] The starting rolling temperature is 950℃, the rough rolling temperature is 1050℃, the pre-finishing rolling temperature is 900℃, the finishing rolling temperature is 840℃, the cooling bed inlet temperature is 840℃, and the final rolling temperature is 880℃.
[0100] Example 6
[0101] A Cu-Cr-Ni corrosion-resistant steel bar, the chemical composition of which includes: C: 0.11wt%, Si: 0.45wt%, Mn: 1.4wt%, Cu: 0.5wt%, Cr: 0.85wt%, Ni: 0.35wt%, V: 0.025wt%, and the rest is Fe and unavoidable impurities.
[0102] The method for preparing the above-mentioned Cu-Cr-Ni corrosion-resistant steel bar comprises:
[0103] Step 1: heating the ingot to 1500°C until the austenite is homogenized and keeping the temperature for 30 minutes to obtain a homogenized steel ingot;
[0104] Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet;
[0105] Step 3: After rolling the billet to the target thickness, air cool it to room temperature.
[0106] The starting rolling temperature is 1050℃, the rough rolling temperature is 1070℃, the pre-finishing rolling temperature is 920℃, the finishing rolling temperature is 860℃, the cooling bed inlet temperature is 860℃, and the final rolling temperature is 950℃.
[0107] Comparative Example 1
[0108] Comparative Example 1 uses commercially available HRB400E steel bars, and tests the yield strength, tensile strength, hardness, elongation, and corrosion rate thereof. The results are shown in Table 1.
[0109] Its yield strength, tensile strength, hardness, elongation and corrosion rate are 435MPa, 613MPa, 208HV, 23%, 3.5098*10 -2 g / (m 2 h).
[0110] The volume fractions of ferrite, pearlite and bainite are 53%, 47% and 0% respectively.
[0111] The test results show that the Cu-Cr-Ni corrosion-resistant steel bar of Example 1 has excellent marine atmospheric corrosion resistance and seawater corrosion resistance, both of which are better than the corrosion resistance of HRB400E. Figure 4 The corrosion morphology of the Cu-Cr-Ni corrosion-resistant steel bars in Example 1 and the ordinary steel bars in this comparative example were immersed in a 3.5wt% NaCl solution for 15 days. Figure 4 It can be seen that the ordinary steel bars in comparative example 1 show pitting corrosion, which causes great damage to the matrix, while the Cu-Cr-Ni corrosion-resistant steel bars in example 1 generate a dense rust layer, which protects the matrix.
[0112] Comparative Example 2
[0113] Comparative Example 2 is basically the same as Example 1, except that the Ni of the Cu-Cr-Ni system in Example 1 is removed to obtain a Cu-Cr corrosion-resistant steel bar. The yield strength, tensile strength, hardness, elongation, and corrosion rate of the steel bar are tested, and the results are shown in Table 1.
[0114] Its yield strength, tensile strength, hardness, elongation and corrosion rate are 482.9MPa, 652.1MPa, 223.22HV, 21.71%, 3.3301*10 -2 g / (m 2 h).
[0115] The volume fractions of ferrite, pearlite and bainite are 52%, 47% and 1% respectively.
[0116] The test results show that after removing Ni from the Cu-Cr-Ni system, the yield strength, tensile strength and hardness of the steel bars obtained are better than those of the commercially available HRB400E steel bars, but are lower than the corrosion-resistant steel bars in Example 1, indicating that Ni has a greater impact on the overall performance of the corrosion-resistant steel bars.
[0117] Comparative Example 3
[0118] Comparative Example 3 is basically the same as Example 1, except that the content of Cr in Example 1 is replaced by 4.44wt%, and the content of Ni is replaced by 0wt%, to obtain a Cu-Cr corrosion-resistant steel bar. The yield strength, tensile strength, hardness, elongation, and corrosion rate of the steel bar are tested, and the results are shown in Table 1.
[0119] Its yield strength, tensile strength, hardness, elongation and corrosion rate are 1053MPa, 1234MPa, 443HV, 11.16%, 3.1737*10 -2 g / (m 2 h).
[0120] Table 1 Performance test results comparison table of the corrosion-resistant steel bars of Example 1 and the steel bars of the comparative example
[0121] Yield strength / MPa Tensile strength / MPa Hardness / HV Elongation / % <![CDATA[Corrosion rate g / m 2 ·h]]> Example 1 560.75 727.35 263.5 17.89 <![CDATA[2.7253*10 -2 ]]> Comparative Example 1 435 613 208 23 <![CDATA[3.5098*10 -2 ]]> Comparative Example 2 482.9 652.1 223.22 21.71 <![CDATA[3.3301*10 -2 ]]> Comparative Example 3 1053 1234 443 11.16 <![CDATA[3.1737*10 -2 ]]>
[0122] Results and analysis: According to Example 1 and Comparative Example 1, the corrosion-resistant steel bars prepared by the present invention have better yield strength, tensile strength and hardness than the commercially available HRB400E steel bars. -2 g / (m 2 The corrosion rate of the corrosion-resistant steel bar of the present invention is 2.7253*10 -2, the corrosion rate is significantly slower. According to Example 1 and Comparative Example 2, after removing Ni from the Cu-Cr-Ni system, the yield strength, tensile strength and hardness of the obtained steel bar are better than those of the commercially available HRB400E steel bar, but are lower than those of the corrosion-resistant steel bar of the present invention, indicating that Ni has a greater impact on the overall performance of the corrosion-resistant steel bar. According to Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that without adding Ni, significantly increasing the Cr content will achieve significantly higher yield strength, tensile strength and hardness, but its corrosion rate is still significantly higher than that of the present invention, indicating that Ni not only affects the yield strength, tensile strength and hardness of the steel bar, but also has a greater impact on the corrosion rate of the steel bar.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A Cu-Cr-Ni corrosion-resistant steel bar, characterized in that: The chemical composition of the Cu-Cr-Ni corrosion-resistant steel bar includes: C: 0.10-0.11wt%, Si: 0.3-0.5wt%, Mn: 1.1-1.5wt%, Cu: 0.3-0.6wt%, Cr: 0.7-0.9wt%, Ni: 0.2-0.4wt%, V: 0.01-0.03wt%, and the rest is Fe and inevitable impurities.
2. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 1, characterized in that: The microstructure of the Cu-Cr-Ni corrosion-resistant steel bar is ferrite+pearlite+a small amount of bainite.
3. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 2, characterized in that: In the microstructure of the Cu-Cr-Ni corrosion-resistant steel bar, the proportion of ferrite is 35% to 45%, the proportion of pearlite is 45% to 58%, and the proportion of bainite is 7% to 18%.
4. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 1, characterized in that: The average corrosion rate of the Cu-Cr-Ni corrosion-resistant steel bar in the 15-day immersion test was 2.6537*10 -2 ~2.8815*10 -2 g / (m 2 h).
5. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 1, characterized in that: The Cu-Cr-Ni corrosion-resistant steel bar has a yield strength of 530MPa-580MPa, a tensile strength of 700MPa-750MPa, a hardness of 250HV-280HV, and an elongation of 16%-19%.
6. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 1, characterized in that: The C: 0.105-0.11wt%, Si: 0.3-0.4wt%, Mn: 1.4-1.5wt%, Cu: 0.3-0.4wt%, Cr: 0.7-0.9wt%, Ni: 0.2-0.4wt%, V: 0.01-0.03wt%, and the rest are Fe and inevitable impurities.
7. The Cu-Cr-Ni corrosion-resistant steel bar according to claim 4, characterized in that: The soaking solution of the soaking experiment was a 3.5 wt % NaCl solution, and the solution was replaced every three days.
8. The method for preparing a Cu-Cr-Ni corrosion-resistant steel bar according to any one of claims 1 to 7, characterized in that: include: Step 1: heating the ingot to the austenite homogenization temperature and keeping the temperature to obtain a homogenized steel ingot; Step 2: performing rough rolling, pre-finish rolling and finish rolling on the steel billet after soaking to obtain a finish rolled steel billet; Step 3: After rolling the billet to the target thickness, cool it to room temperature.
9. The method for preparing a Cu-Cr-Ni corrosion-resistant steel bar according to claim 8, characterized in that: The austenite homogenization temperature is 1150-1500°C and the holding time is 30-50 minutes.
10. The method for preparing a Cu-Cr-Ni corrosion-resistant steel bar according to claim 8, characterized in that: The starting rolling temperature is not less than 900℃, the rough rolling temperature is 1050±20℃, the pre-finishing rolling temperature is 910±20℃, the finishing rolling temperature is 850±20℃, the cooling bed inlet temperature is 850±20℃, and the final rolling temperature is 850~950℃.
Citation Information
Patent Citations
Preparation process of Cu-Cr series corrosion-resistant steel bars
CN112391572A
RE-Cr-Cu composite corrosion-resistant steel and preparation method thereof
CN112662948A
Preparation process of Cu-Cr corrosion-resistant reinforcing steel bar
CN113897472A